A hybrid kinetic and constraint‐based model of leaf metabolism allows predictions of metabolic fluxes in different environments. (19th November 2021) - Shameer, Sanu; Wang, Yu; Bota, Pedro; Ratcliffe, R. George; Long, Stephen P.; Sweetlove, Lee J.
SUMMARY: While flux balance analysis (FBA) provides a framework for predicting steady‐state leaf metabolic network fluxes, it does not readily capture the response to environmental variables without being coupled to other modelling formulations. To address this, we coupled an FBA model of 903 reactions of soybean ( Glycine max ) leaf metabolism with e‐photosynthesis, a dynamic model that captures the kinetics of 126 reactions of photosynthesis and associated chloroplast carbon metabolism. Successful coupling was achieved in an iterative formulation in which fluxes from e‐photosynthesis were used to constrain the FBA model and then, in turn, fluxes computed from the FBA model used to update parameters in e‐photosynthesis. This process was repeated until common fluxes in the two models converged. Coupling did not hamper the ability of the kinetic module to accurately predict the carbon assimilation rate, photosystem II electron flux, and starch accumulation of field‐grown soybean at two CO2 concentrations. The coupled model also allowed accurate predictions of additional parameters such as nocturnal respiration, as well as analysis of the effect of light intensity and elevated CO2 on leaf metabolism. Predictions included an unexpected decrease in the rate of export of sucrose from the leaf at high light, due to altered starch–sucrose partitioning, and altered daytime flux modes in the tricarboxylic acid cycle at elevated CO2 . Mitochondrial fluxes were notably different between growing and mature leaves, with greater anaplerotic, tricarboxylic acid cycle and mitochondrial ATP synthase fluxes predicted in the former, primarily to provide carbon skeletons and energy for protein synthesis. Significance Statement: A model of the relationship between photosynthesis and other metabolic pathways in soybean leaves was constructed by coupling a kinetic model of photosynthesis with a constraint‐based stoichiometric model of the rest of leaf metabolism. The new modelling formulation is shown, by comparison with measurements, to allow a broad prediction of leaf metabolic behaviour under different environments and will be a useful tool for guiding strategies for improving leaf carbon and energy‐use efficiency under global change.